Mortimer's first garden - Wilson, Karma (Margaret K. McElderry Books, 2009)
Little Mortimer Mouse, longing to see something green at winter's end, follows the lead of the big people and plants, waters, and weeds his last sunflower seed until, finally, with God's help and a lot of patience, he harvests his crop.